Multi-objective optimization of organic Rankine cycle systems considering their dynamic performance - Pili, Roberto; Bojer Jørgensen, Søren; Haglind, Fredrik (Energy (Oxford), 2022)
The Organic Rankine cycle system is a well-established technology for converting the waste heat from internal combustion engines into mechanical or electrical power. For a vehicle, due to the engine load changes during the driving cycle, the mass flow rate and temperature of the waste heat fluctuate rapidly over a broad range. This poses high requirements to the control of the organic Rankine cycle unit, in order to ensure safety, high efficiency, system compactness and long component lifetime. This paper presents a novel design method for organic Rankine cycle systems subject to highly fluctuating heat sources, ensuring safe and efficient operation. An integral optimization code developed in MATLAB®/Simulink® combining the design of the thermodynamic cycle, the system evaporator and the control system with a dynamic simulation model is presented. The multi-objective optimization maximizes the organic Rankine cycle net power output over a driving cycle of a heavy-duty truck, while minimizing the mass of the evaporator. The results indicate that, in order to ensure safe operation, the degree of superheating of the working fluid as well as the exhaust gas temperature leaving the evaporator at design conditions should be higher than what classical steady-state thermodynamic analyses suggest. •Multi-objective optimization of organic Rankine cycle systems including dynamics.•Trade-off between maximum net power output and minimum component mass.•Unfeasible designs result from classical optimization at time-weighted average.•Including the dynamic performance leads to a 35 K higher design superheating.•Toluene, ethanol and pentane resulted in the best working fluids.